ANALISIS VARIABEL KEPEMIMPINAN, IKLIM ORGANISASI, KOMUNIKASI DAN BUDAYA NASIONAL YANG MEMPENGARUHI KINERJA KARYAWAN - Rio Leanderita Farindra; Noermijati - -; Djumilah - Zain (Sekolah Pascasarjana Universitas Brawijaya, 2009)
ABSTRACT This research aims at knowing and analyzing leadership variable, organizational climate, national culture and communication that influencing the employee performance. The sample in this research used 112 respondent and stratified random sampling at government of regency Muara-Enim. This research used factor analyses and multiple regression to know variable that influence the employee performance. Result of research indicate: (1) leadership factor, organizational climate, national culture and communications in local government by simultan have an effect on to employees performance. (2) By parsial only the organizational climate factor and the communications having an signifikan effect to employees performance at local government. (3) Result of correlation analysis between leadership variable And organizational climate indicate that leadership variable own relation which are positive to organizational climateKeywords : Kepemimpinan, Iklim Organisasi, Komunikasi, Budaya Nasional, Kinerja. Keywords: local government, leadership, performance